Spinal Anesthesia for Cesarean Section in a Patient with Total AV Block - Agiel Fahlevie Choirunanda; I Made Subagiartha (Journal of Social Research, 2025)
Anesthetic management in obstetric patients with heart disease, especially Total Atrioventricular (AV) Block, is a major challenge due to the high risk of hemodynamic collapse and maternal mortality. This condition requires a very careful approach to anesthesia, especially in patients with comorbid preeclampsia. This case study aims to describe a safe spinal anesthesia management strategy in pregnant patients with Total AV Block without the installation of a prophylactic pacemaker. A 31-year-old female patient with G2P1001 at 37+6 weeks gestation, diagnosed with Superimposed Preeclampsia with Total AV Block, underwent emergency cesarean section. Preoperative evaluation showed a pulse rate of 38–55 bpm and evidence of total AV block on the ECG. The anesthesia procedure uses spinal with a low dose 0.5% Bupivacaine Heavy (10 mg) to limit the sensory block at the T5 level from hitting the heart accelerator fibers. Throughout surgery, the patient's hemodynamics are stable with tolerable fluctuations in blood pressure and pulse. Interestingly, the administration of 0.5 mg of atropine still produced an increased response in heart rate and blood pressure although it was generally ineffective in total AV blocks. The surgery took place safely, the baby was born with a good Apgar score, and the patient was admitted to the postoperative ICU for strict monitoring. In conclusion, low-dose spinal anesthesia can be a safe option in patients with Total AV Block with rigorous preparation, intensive monitoring, and emergency pacemaker readiness.